2013
DOI: 10.1080/09205063.2013.833441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural response of a hybrid hydrogel based on chitosan and poly(vinyl alcohol) cross-linked with epichlorohydrin for potential use in tissue engineering

Abstract: The development and characterization of a hybrid hydrogel based on chitosan (CS) and poly(vinyl alcohol) (PVA) chemically cross-linked with epichlorohydrin (ECH) is presented. The mechanical response of these hydrogels was evaluated by uniaxial tensile tests; in addition, their structural properties such as average molecular weight between cross-link points (Mcrl), mesh size (DN), and volume fraction (v(s)) were determined. This was done using the equivalent polymer network theory in combination with the obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…It was observed that the mobility and deformation of their polymeric chains were significantly reduced; hence, the network lost water absorption capability. Comparing the swelling behavior 330 between CS/PVA with the CS/PVA/GA and CS/PVA/GEN blends, it was found that the overshooting effect, which was reported for CS and CS/PVA blend by Garnica-Palafox et al (2014), was inhibited because of the chemical crosslinking reagents. considerable effect on the hydrophilicity of these hydrogels (64 ± 1 • and 63 ± 1 • , respectively).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…It was observed that the mobility and deformation of their polymeric chains were significantly reduced; hence, the network lost water absorption capability. Comparing the swelling behavior 330 between CS/PVA with the CS/PVA/GA and CS/PVA/GEN blends, it was found that the overshooting effect, which was reported for CS and CS/PVA blend by Garnica-Palafox et al (2014), was inhibited because of the chemical crosslinking reagents. considerable effect on the hydrophilicity of these hydrogels (64 ± 1 • and 63 ± 1 • , respectively).…”
mentioning
confidence: 86%
“…However, the long-term structural and mechanical stability of the blend is still an issue. To address this issue, chemical crosslink- 30 ing reagents have been used (glutaraldehyde He & Xiong (2012); Hu et al A c c e p t e d M a n u s c r i p t (2013), epichlorohydrin Garnica-Palafox et al (2014) and genipin Khurma et al (2006); Bispo et al (2010)). Recent efforts have demonstrated that the physicochemical properties of CS can be tuned, which has been achieved by combining CS with other polymers or using chemical crosslinkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future development of synthetic scaffolds should focus on continued development of protein-based electrospun constructs, and implantation of these constructs in VML injury models [46,47,49]. Hybrid micropatterned and electrospun substrates are being adapted to promote the growth and differentiation of MPCs, while studies using modified hydrogels are incorporating structural proteins such as fibrin and chitosan to better replicate the progenitor cell niche in vitro [50,69,70]. Future studies using native protein-based scaffolds should focus on shaping these technologies for use in skeletal muscle VML injury models.…”
Section: Future Perspectivementioning
confidence: 99%
“…Crosslinking with epichlorohydrin (ECH) can be cited as an example of the chitosan chemical modifications carried out in order to prevent its dissolution in acidic solutions. Crosslinking CS-PVA with ECH brings more construction stability through formation of a polymeric tridimensional network increasing its lifespan (Garnica-Palafox et al, 2014). The aim of our study was to evaluate the biocompatibility of human microtic auricular chondrocytes with a CS-PVA-ECH based hydrogel in order to propose this material as a scaffold to support and promote neotissue formation.…”
Section: Introductionmentioning
confidence: 99%